2020
DOI: 10.1186/s12951-020-00744-w
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid-coated polymeric micelles with hydrogen peroxide scavenging to encapsulate statins for alleviating atherosclerosis

Abstract: Inflammation and oxidative stress are two major factors that are involved in the pathogenesis of atherosclerosis. A smart drug delivery system that responds to the oxidative microenvironment of atherosclerotic plaques was constructed in the present study. Simvastatin (SIM)-loaded biodegradable polymeric micelles were constructed from hyaluronic acid (HA)-coated poly(ethylene glycol)-poly(tyrosine-ethyl oxalyl) (PEG-Ptyr-EO) for the purpose of simultaneously inhibiting macrophages and decreasing the level of re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Using HA–coated nanocomplexes decorated with lectin-like oxidized low-density lipoprotein receptor (LOX-1) siRNA cell-penetrating peptides, Zhao et al demonstrated reductions in plaque area by 28% and neutral lipid content by 37%, as well as less infiltration of macrophages and chemokines in ApoE −/− mice [ 113 ]. Mu et al loaded simvastatin into biodegradable HA-coated polymeric micelles and found that treatment with these particles resulted in significantly reduced plaque size in ApoE −/− mice on HFD [ 114 ]. In these studies, HA may have also played an anti-oxidative role further improving the observed therapeutic effects.…”
Section: Strategies For Targeting Atherothrombosismentioning
confidence: 99%
“…Using HA–coated nanocomplexes decorated with lectin-like oxidized low-density lipoprotein receptor (LOX-1) siRNA cell-penetrating peptides, Zhao et al demonstrated reductions in plaque area by 28% and neutral lipid content by 37%, as well as less infiltration of macrophages and chemokines in ApoE −/− mice [ 113 ]. Mu et al loaded simvastatin into biodegradable HA-coated polymeric micelles and found that treatment with these particles resulted in significantly reduced plaque size in ApoE −/− mice on HFD [ 114 ]. In these studies, HA may have also played an anti-oxidative role further improving the observed therapeutic effects.…”
Section: Strategies For Targeting Atherothrombosismentioning
confidence: 99%
“…The rationale to develop peptidomimetics to mimic the protective role or block detrimental actions of ECM molecules for the plaque was described by Lv et al [ 16 ▪▪ ] for COMP. In addition, several studies have employed CD44-hyaluronan interactions for targeting atherosclerosis, designing hyaluronan-coated polymeric micelles targeting CD44 overexpressing macrophages [ 22 , 23 ]. Further research is needed to characterise proteoglycan remodelling by degrading enzymes for example proteoglycanases, heparinase, at different stages of the atherosclerosis, introducing novel targets or biomarkers.…”
Section: Proteoglycans and Their Glycosaminoglycans In Atherosclerosismentioning
confidence: 99%
“…Some polymers have also been exploited as antioxidants, and their ROS-quenching effect is mainly attributed to their special structures and inherent catalytic properties. An amphiphilic block copolymer, poly(ethylene glycol)–poly(tyrosine-ethyl oxalyl), was synthesized and self-assembled into micelles loaded with simvastatin, a kind of statin drug with antioxidant and anti-inflammatory effects [ 82 , 83 , 84 ]. This kind of micelle can consume ROS in pathologic sites and exert a synergistic antioxidant effect with simvastatin.…”
Section: Ros-sensitive Nano-formulations For Atherosclerosis Applicationsmentioning
confidence: 99%
“…This kind of micelle can consume ROS in pathologic sites and exert a synergistic antioxidant effect with simvastatin. Intravenous administration of micelles in ApoE −/− mice can efficiently reduce the lesion area of plaque, showing great therapeutic effects on atherosclerosis [ 84 ]. Another case is represented by PBAPs that can be oxidized by H 2 O 2 to generate phenolic compounds.…”
Section: Ros-sensitive Nano-formulations For Atherosclerosis Applicationsmentioning
confidence: 99%